Assessment of groundwater salinity and quality in Gaza coastal aquifer, Gaza Strip, Palestine: An integrated statistical, geostatistical and hydrogeochemical approaches study - Abu-alnaeem, Madhat Farouk; Yusoff, Ismail; Ng, Tham Fatt; Alias, Yatimah; Raksmey, May (Elsevier, 2018)
A comprehensive study was conducted to identify the salinization origins and the major hydrogeochemical processes controlling the salinization and deterioration of the Gaza coastal aquifer system through a combination approaches of statistical and geostatistical techniques, and detailed hydrogeochemical assessments. These analyses were applied on ten physicochemical variables for 219 wells using STATA/SE12 and Surfer softwares. Geostatistical analysis of the groundwater salinity showed that seawater intrusion along the coastline, and saltwater up-coning inland highly influenced the groundwater salinity of the study area. The hierarchical cluster analysis (HCA) technique yielded seven distinct hydrogeochemical signature clusters; (C1&C2: Eocene brackish water invasion, C3 saltwater up-coning, C4 human inputs, C5 seawater intrusion, C6 & C7 rainfall and mixing inputs). Box plot shows a wide variation of most of the ions while Chadha's plot elucidates the predominance of Na-Cl (71.6%) and Ca/Mg-Cl (25%) water types. It is found that, the highest and the lowest levels of salinization and the highest level of nitrate pollution were recorded in the northern area. This result reflects the sensitivity of this area to the human activities and/or natural actions. Around 90.4% of the wells are nitrate polluted. The main source of nitrate pollution is the sewage inputs while the farming inputs are very limited and restricted mostly in the sensitive northern area. Among the hydrogeochemical processes, ion exchange process was the most effective process all over the study area. Carbonate dissolution was common in the study area with the highest level in clusters 6, 7, 4 and 2 in the north while Gypsum dissolution was significant only in cluster 1 in the south and limited in the other clusters. This integrated multi-techniques research should be of benefit for effective utilization and management of the Gaza coastal aquifer system as well as for future work in other similar aquifers systems.